Epithelial zinc finger protein in lung adenocarcinoma: prognostic biomarker with molecular and clinical implications - Xiaofen Wen; Jianling Zhu; Didi Xi; Minna Chen; De Zeng; Wenwu Xue; Danxia Lin; Jiaxin Shen (Hereditas)
Abstract Objective This study aimed to evaluate the prognostic significance of epithelial zinc finger protein (EZF/KLF4) in lung adenocarcinoma (LAC) and explore its potential roles in tumor progression and immune regulation. Methods and Materials EZF expression and its associations with clinical characteristics were analyzed using TCGA and GEO datasets, and validated by immunohistochemistry in 25 paired LAC and adjacent normal tissues. Mechanistic insights were investigated through protein–protein interaction networks, gene set enrichment analysis (GSEA), DNA methylation profiling, and immune cell infiltration analysis via single-sample GSEA. A prognostic nomogram incorporating EZF expression, pT and pN stages, and residual tumor status was constructed using Cox regression modeling. Results EZF expression was significantly downregulated in LAC tissues compared to normal tissues across multiple cohorts (P < 0.001), yet paradoxically associated with advanced tumor stages and worse overall, disease-specific, and progression-free survival. Functional analyses revealed EZF-associated pathways enriched in immune modulation. EZF expression correlated strongly with infiltrating immune cells, including NK cells, eosinophils, mast cells, and neutrophils. Hypomethylation of the EZF promoter was linked to poor prognosis. The constructed nomogram exhibited strong predictive accuracy for patient outcomes. Conclusion EZF functions as a context-dependent regulator in LAC and may act as a prognostic biomarker by modulating tumor-immune interactions. These findings offer novel insights into the integration of molecular and immune features for personalized risk stratification and therapeutic guidance in LAC.